Dynamic contrast-enhanced MRI measurement of renal function in healthy participants. (June 2017) - Eikefjord, Eli; Andersen, Erling; Hodneland, Erlend; Hanson, Erik A; Sourbron, Steven; Svarstad, Einar; Lundervold, Arvid; Rørvik, Jarle T
Background: High repeatability, accuracy, and precision for renal function measurements need to be achieved to establish renal dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) as a clinically useful diagnostic tool. Purpose: To investigate the repeatability, accuracy, and precision of DCE-MRI measured renal perfusion and glomerular filtration rate (GFR) using iohexol–GFR as the reference method. Material and Methods: Twenty healthy non-smoking volunteers underwent repeated DCE-MRI and an iohexol–GFR within a period of 10 days. Single-kidney (SK) MRI measurements of perfusion (blood flow, Fb ) and filtration (GFR) were derived from parenchymal intensity time curves fitted to a two-compartment filtration model. The repeatability of the SK-MRI measurements was assessed using coefficient of variation (CV). Using iohexol–GFR as reference method, the accuracy of total MR–GFR was determined by mean difference (MD) and precision by limits of agreement (LoA). Results: SK-Fb (MR1, 345 ± 84; MR2, 371 ± 103 mL/100 mL/min) and SK–GFR (MR1, 52 ± 14; MR2, 54 ± 10 mL/min/1.73 m 2 ) measurements achieved a repeatability (CV) in the range of 15–22%. With reference to iohexol–GFR, MR–GFR was determined with a low mean difference but high LoA (MR1, MD 1.5 mL/min/1.73 m 2, LoA [−42, 45]; MR2, MD 6.1 mL/min/1.73 m 2, LoA [−26, 38]). Eighty percent and 90% of MR–GFR measurements were determined within ± 30% of the iohexol–GFR for MR1 and MR2, respectively. Conclusion: Good repeatability of SK-MRI measurements and good agreement between MR–GFR and iohexol–GFR provide a high clinical potential of DCE-MRI for renal function assessment. A moderate precision in MR-derived estimates indicates that the method cannot yet be used in clinical routine.